2021
DOI: 10.1155/2021/8886525
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features, Endoscopic Findings, and Predictive Factors for Mortality in Tissue-Invasive Gastrointestinal Cytomegalovirus Disease between Immunocompetent and Immunocompromised Patients

Abstract: Background and Aims. Tissue-invasive gastrointestinal cytomegalovirus (TI-GI CMV) disease is common in immunocompromised patients, but the increasing prevalence in immunocompetent patients has been reported. This study compared the clinical manifestations, endoscopic features, treatment outcomes, and predictors for inhospital mortality of TI-GI CMV between immunocompromised and immunocompetent patients. Methods. Patients with HIV infection, malignancy, or receiving immunosuppressive agents (chemotherapy, high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 39 publications
(77 reference statements)
0
30
2
Order By: Relevance
“…In host status, old age, immunocompromised status, and malnutrition (hypoalbuminemia) resulted in impaired immune function and then poor survival. In two prior studies, old age and malnutrition were noted as negative predictive factors for mortality as well [7,9]. Since hypoalbuminemia indicates malnourishment, poor immunity, and worse tissue healing, it is responsible for increased mortality rates in several diseases, especially in patients in the ICU setting [25][26][27].…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…In host status, old age, immunocompromised status, and malnutrition (hypoalbuminemia) resulted in impaired immune function and then poor survival. In two prior studies, old age and malnutrition were noted as negative predictive factors for mortality as well [7,9]. Since hypoalbuminemia indicates malnourishment, poor immunity, and worse tissue healing, it is responsible for increased mortality rates in several diseases, especially in patients in the ICU setting [25][26][27].…”
Section: Discussionmentioning
confidence: 97%
“…With regard to immunocompromised status, Wetwittayakhlang et al reported no significant difference in in-hospital survival, while Chaemsupaphan et al noted that the six-month mortality was higher in immunocompetent patients. These discrepant results might be associated with differences in patient selection (IHC staining, definition of immunocompromised status), study endpoints (disease-specific mortality or overall mortality), and treatment strategies [7,9]. Second, thrombocytopenia and GI bleeding were negative predictors of in-hospital mortality.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations